Abundancia estacional y distribución espacial de Misidacea en el Atlántico Sudoccidental - Cardelli Natalia (2006)
Two mysids species were present in the Bahia Blanca estuary: Arthromysis magellanica (Cunningham) and Neomysis americana (Smith). They were present in the estuary from August to March. The abundance of A. magellanica was highest, 31.92 ind.m -3 in spring and N. americana abundance reached a maximum of 10.91 ind.m -3 during midsummer. These high abundance values were coincident with the increment of the water temperature. The mean temperature value registered during the sa mpled period was 15.7°C. Both species were present from 10°C to 23.3°C and were absent from 6.6°C to 22°C . In agreement with the spatial distribution of both species, a relationship in the abundance of A. magellanica for the three sampling stations was not detected (ANOVA, n=8, P> 0.80) but there was a relationship in the abundance of N. americana for the three sampling stations (ANOVA, n=10, P< 0.05) since the highest density of this species was recorded in the inner zone of the estuary. Significant differences in salinity were found between the three sampling stations for those dates when N. americana was present (ANOVA, n=10, P< 0.05) but it could not be demonstrated that this variable is related with the spatial distribution of this species in the estuary (covariable, P> 0.15).